Yield Qualities Evaluation for Gayo Arabica Coffee Germplasm. Issue 1 (1st June 2022) - Samsudin,; Iflah, T; Syafaruddin,; Ferry, Y
Abstract: Gayo Arabica coffee has been known in the world market as specialty coffee. Some lines of Arabica coffee that have been planted in the Gayo Experimental Station (GES) for more than 20 years have the potential to be released as superior varieties. This study aimed to evaluate the physical, physicochemical and organoleptic qualities of 15 Arabica coffee lines in the GES germplasm. The physical quality test of beans refers to SNI 2907-2008 by observing the length, width, thickness, and weight of 100 beans. Physicochemical content testing was carried out on beans, including caffeine, protein, fat, and ash. Organoleptic testing was carried out by certified panelists referring to the Specialty Coffee Association of America (SCAA) standards. The evaluation results of 15 Gayo Arabica coffee lines showed that all lines had the good physical quality of beans. Protein content ranges from 10.79-14.14%, caffeine 0.51-0.82, and fat 12.48-15.68%. All tested Arabica coffees had a total score of more than 80, which means they are included in the specialty category. The Ateng Super, C 49, and SLN 9 lines had a better taste (85.75) than the superior varieties released, namely Gayo 1 (83.75) and Gayo 2 (85.50).